Investigating the hidden geometry system at the entrance of the historical houses of Kashan from the Qajar period to the beginning of the Pahlavi period - Danaeinia, Ahmad; Erfan, Bahador; Mohamadi Sabet, Zeynab (Journal of Architecture and Urbanism, 2024)
Geometry is one of the most important aspects hidden in the design of historical buildings in a way, it can be said that architecture without the presence of geometry is meaningless and lacks functional validity. The ratio and proportion that can be seen in the entrance and front facade of the historical houses of Kashan is a function of geometry, which is named hidden geometry in this research. The geometric system at the entrance of historical houses is one of the most important topics that help to better understand the historical building. The findings show that the entrance design of the houses is under the hidden geometry system, and five types of geometric systems are used to shape it, including symmetry, Fibonacci in golden triangles, Fibonacci in golden rectangles, dynamic rectangles, and regular polygons.